Terapi Komplementer untuk Penatalaksanaan Kecemasan atau Depresi pada Lansia yang Tinggal di Komunitas - Arjuna Arjuna; Etty Rekawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine complementary therapies that can be applied to managing anxiety and depression in the elderly in the community. Methods for searching articles through English databases: EBSCO host, Scopus, Pro-Quest, Wiley Online Library, Sage Publications, Science direct, and Springer Link in the last ten years. The search results obtained 282 articles, and six reports identified that met the inclusion criteria. Systematic review analysts use the PRISMA diagram. There are six complementary therapies used: aromatherapy, reiki, laughter therapy, acupressure, religion, aromatherapy, music, and reiki. In conclusion, all of these complementary therapies are effective in the management of anxiety or depression. The complementary treatment suggested in the direction of pressure is aromatherapy, while depression is religious therapy. Keywords: Depression, Anxiety, Parents, Complementary Therapy